Pengembangan Aplikasi Rekomendasi Pet Shop Berbasis Android Menggunakan Arsitektur MVVM (Model-View-Viewmodel) (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
At this time, keeping pets such as cats has become a lifestyle for pet lovers, sometimes many consider these pets as their own family. Therefore, pet owners always provide the best care for their beloved animals. Sometimes people are confused about which place is the best for their pet, which one is cheaper, which one is suitable for the type of pet, the benefits, and the location is not too far away. This system uses one of the methods in the Decision Support System. By using the Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods in a Decision Support System, it is hoped that it can help solve problems in semi-structured areas such as the problems above. This study aims to assist users in determining which pet shop they want to visit.